2015
DOI: 10.1021/acs.analchem.5b01560
|View full text |Cite
|
Sign up to set email alerts
|

Label-Free SERS Selective Detection of Dopamine and Serotonin Using Graphene-Au Nanopyramid Heterostructure

Abstract: Ultrasensitive detection and spatially resolved mapping of neurotransmitters, dopamine and serotonin, are critical to facilitate understanding brain functions and investigate the information processing in neural networks. In this work, we demonstrated single molecule detection of dopamine and serotonin using a graphene–Au nanopyramid heterostructure platform. The quasi-periodic Au structure boosts high-density and high-homogeneity hotspots resulting in ultrahigh sensitivity with a surface enhanced Raman spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
107
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 165 publications
(110 citation statements)
references
References 43 publications
3
107
0
Order By: Relevance
“…121 They also reported the detection of these neurotransmitters at concentrations as low as 10 −9 M in simulated body fluids supplemented with background serum proteins. The dominant vibrational band for dopamine was associated with the C=C stretching mode.…”
Section: Metabolitesmentioning
confidence: 97%
See 1 more Smart Citation
“…121 They also reported the detection of these neurotransmitters at concentrations as low as 10 −9 M in simulated body fluids supplemented with background serum proteins. The dominant vibrational band for dopamine was associated with the C=C stretching mode.…”
Section: Metabolitesmentioning
confidence: 97%
“…It was reported that the π-π interactions between the ring structures and the graphene contributed to the chemical enhancement. 121 Bailey et al detected the neurotransmitters: dopamine, serotonin, norepinephrine, epinephrine, and catechol to investigate the role of surface absorption in SERS. 122 The dominant vibrational bands were associated with phenol moiety, which suggest that this area of the neurotransmitter adsorbs to the SERS active-surface.…”
Section: Metabolitesmentioning
confidence: 99%
“…Even in unpurified samples, single picomolar concentrations can be measured [155]. There is a variety of detected molecules, including TNT [155], neurotransmitters dopamine and serotonin [156], and incubated Escherichia coli [157]. Label-free SERS assays have also been developed using PDMS in an integrated microfluidic device for biomolecular detection [158].…”
Section: Label-free Assaysmentioning
confidence: 99%
“…For 2D materials used in hybrid SERS platform with patterned metallic SERS nanostructures, graphene is the ideal choice because graphene only has a few intrinsic Raman peaks and large-area high quality graphene is easily achievable. Another benefit of graphene is that its intrinsic peak intensity could be used to quantify the analytes [20,22].…”
Section: Two-dimensional Materials Combined With Metallic Nanostructuresmentioning
confidence: 99%
“…Two-dimensional (2D) materials, such as graphene and molybdenum disulfide (MoS 2 ), have unique electronic and optical properties and thus attract wide interests in their potential applications in electronic devices, sensors, and energy generation [13][14][15][16][17][18]. In addition to the above-mentioned applications, graphene and other 2D materials have also been explored to enhance Raman signals [13,[19][20][21][22]. Since the discovery of graphene's Raman enhancement capability [23], extensive researches have been done to reveal the enhancing mechanism of twodimensional materials, as well as their application in Raman enhancement either with bare 2D material substrate or with hybrid metal/2D material substrate [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%